Modeling communication of collaborative multiagent system under epistemic planning. Issue 10 (16th June 2021) - Alshehri, Abeer; Miller, Tim; Sonenberg, Liz
Abstract: In most multiagent applications, communication is essential among agents to coordinate their actions and achieve their goals. However, communication often has a related cost that affects overall system performance. In this paper, we draw inspiration from epistemic planning studies to develop a communication model for agents that allows them to cooperate and make communication decisions effectively within a planning task. The proposed model treats a communication process as an action that modifies the epistemic state of the team. We evaluate whether agents can cooperate effectively and achieve higher performance using communication protocol modeled in our epistemic planning framework in two simulated tasks. Based on an empirical study conducted using search and rescue tasks with different scenarios, our results show that the proposed model improved team performance across all scenarios than baseline models.